HOLD YOUR HORSES! UNDERSTANDING THE RELATIONSHIP BETWEEN STRATEGIC CHANGE AND JOB BURNOUT AMONG LECTURERS IN MALAYSIAN HIGHER EDUCATION INSTITUTIONS - Nur Fatihah Shaari; Amir Imran Zainoddin; Muhammad Majid; Ahmad Syahmi Ahmad Fadzil; Al Amirul Eimer Ramdzan; Nur Ain Syazmeen Ahmad Zaki (International Journal of Accounting, Finance and Business, 2023)
In recent years, Malaysia's higher education landscape has undergone significant transformations. Higher education institutions have enhanced their strategic planning with new initiatives to respond to these changes and maintain competitiveness to remain viable and significant. Although these changes are anticipated to align with future requirements, the impact of such a strategic change should be evaluated holistically on every conceivable metric to eliminate the possibility of harm. Numerous studies indicate that such a transformation can negatively affect academics' wellbeing, particularly job burnout. This study aims to conceptually investigate the factors that contribute to job burnout among lecturers within the context of strategic transformation initiatives in higher education institutions in Malaysia. The study was conducted by reviewing secondary data sources from academic publications identified through word searches on "strategic change", "job burnout", and "higher education institutions". The identified articles were subsequently screened for appropriate titles, abstracts, keywords, and frameworks. The relevance of previous studies and the authors' credentials have become this study's selection criteria. A conceptual model was developed based on the criteria outlined for a conceptual paper. Findings indicated that teaching-research conflict, humour and workload could influence job burnout among lecturers. Future research should be conducted based on the proposed instruments to validate the conceptual framework.